Dynamics of Dissolved Carbon in the Mainstem of the Lena River in July 2017; Doklady Earth Sciences; Vol. 500, iss. 2 - Pipko I. I. Irina Ivanovna; Pugach S. P. Svetlana Petrovna; Moiseeva Yu. A. Yuliya Aleksandrovna; Dudarev O. V. Oleg Viktorovich; Repina I. A. Irina; Sergienko V. I. Vladimir Ivanovich; Semiletov I. P. Igor Petrovich (Geochemistry, 2021)
Title screen